HIGH MATRIX METALLOPROTEINASE 9 EXPRESSION AS A RISK FACTOR OF LYMPHOVASCULAR INVASION IN CERVICAL CARCINOMA - Ni Wayan Armerinayanti (Meditory : The Journal of Medical Laboratory, 2025)
Background: Cervical carcinoma is an epithelial cancer with the highest mortality among female genital malignancies. Its poor prognosis is largely related to metastasis, which begins early through lymphovascular space invasion (LVSI). LVSI occurs when cancer cells invade surrounding tissue via proteolytic enzymes, but early prediction remains difficult. Although several molecular markers have been studied, none is definitive, and the role of matrix metalloproteinase-9 (MMP-9) in LVSI remains controversial.Objective: This study will prove MMP-9 as a risk factor for LVSI in cervical carcinomaMethods: This case–control study analyzed 40 archived paraffin-embedded tissue blocks from cervical carcinoma patients at BaliMed Denpasar Hospital. Immunohistochemical staining was performed to assess MMP-9 expression, while hematoxylin and eosin (H&E) staining was used to evaluate lymphovascular space invasion (LVSI). Statistical analysis was conducted using the chi-square test in SPSS version 25.Results: The study showed that 85,7% of cervical carcinomas with LVSI have high MMP-9 expression, with a significant result compared to cervical cancer without LVSI (p=0.001, OR= 13.5).Conclusions: The MMP-9 expression was significantly associated with the risk of LVSI in cervical carcinoma